Mental Health Problems in High School Students and Their Information Channels - A Cross Sectional Study in Bac Giang, Can Tho and Da Nang - Le Thu Hien; Bui Phuong Thao (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
In recent years, mental health and psychosocial problems have both been on the rise in Vietnam, especially among children and young people (ODI and UNICEF 2011). Based on the analysis of quantitative and qualitative data of the ministry-level project "Research on activities to support mental health awareness raising for high school students" (code ĐT.KXĐTN 20-09) issued by the Vietnam Youth Academy in 2020, the article aimed at identifying mental health problems and information channels commonly used by high school students to raise awareness of mental health issues and describes the relationship between these two. The results of the analysis show that students are facing negative mental health symptoms, focusing on two problems with peer relationship, hyperactivity problems. Prosocial activity for them is at the borderline and abnormally high compared to other issues. High school students seek information related to mental health through the three most information channels, respectively: through internet sites; through a mental health mobile app; and shared by parents. The research also shows that there are differences between boys, girls, and grade levels in the use of information channels to learn about mental health. Received 20th October 2022; Revised 17th February 2023; Accepted 9th March 2023